Do school-based violence interventions improve educational outcomes? A systematic review - Karen Devries; Emily Eldred; Jodie Pearlman; Charles Opondo; Anja Zinke-Allmang; Matthew Amollo; Sophie Norman; Shanaaz Mathews; Dipak Naker; Amiya Bhatia (BMC Public Health, 2026)
Abstract Background Education is a key social determinant of health and improving access to quality education is Sustainable Development Goal 4. Unfortunately, many children experience violence in and around schools. Although many school-based violence prevention interventions are effective in prevention of violence and improving school climate, they are still not widely implemented globally in the education sector. This may be because it is unclear whether preventing violence at school improves children’s educational outcomes. We aimed to 1) document whether school-based violence prevention interventions measure educational outcomes and describe what these are; and 2) summarise evidence on effect of school violence interventions on educational outcomes. Methods We drew on a larger systematic review of randomised controlled trials of school-based interventions to prevent violence, with searches until June 2025. We screened 188 papers for any papers that also reported on any educational outcomes. We summarised risk of bias and results narratively and visualised intervention effects on educational outcomes on a forest plot. Results We identified 16 papers reporting on 15 intervention trials. Thirteen of fifteen interventions trialled reduced violence. Six interventions showed an improvement in educational outcomes; four showed mixed results on educational outcomes; five showed no effect. No trials showed a clear and consistent effect of any violence intervention on literacy or numeracy test scores. Five of the six interventions improving educational outcomes were trialled in high income countries. Conclusions School-based violence prevention interventions can improve some educational outcomes for children in high-income settings. In less well-resourced settings, preventing violence may not be sufficient to improve educational outcomes without other interventions. There is no evidence that violence prevention programmes negatively impact educational outcomes. Trial registration PROSPERO CRD42023463384.